(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
Ludovico Quaroni, a native Roman, was a master of Italian architecture during the second half of the twentieth century; his talent contributed to the education – in addition to the majority of the younger generations of architects in Italy – of Carlo Aymonino, Manfredo Tafuri and Antonino Terranova. He also constituted one of the fundamental references to the elaboration of Aldo Rossi’s theories on the city. An architect and urban planner, professor and author, Quaroni represents the most open and inclusive methodological and linguistic experimentalism and the most progressive identity of modern Italian architecture, founded on the close relationship between historic culture, social and contextual awareness, a scientific understanding of design and a passionate investigation of the future; courageous and unbridled. In adopting his name for the review presented today, the Scientific Society intends to return to the discussion of the Architecture of Cities at a time when methodologies, technologies, relationships between the scales of design, the formal and symbolic meanings and languages of the city, everything about which modern Western urban culture appeared certain, now appear overrun by the vertiginous nature of the most rapid and imposing urban expansion in human history, sweeping across both ancient and new continents.